Kinetic facade design to enhance daylight performance for office building in Malaysia - Moesas, Omran Subhi; Alias, Nor Azlina; Azlan, Aznida (Springer, 2021)
Daylight design performance is a significant architectural factor and facade design has a great effect on its performance. In order to predict environmental changes and achieve more efficiently behaviour, kinetic facade is an architectural approach that use for higher effectiveness. This paper presents a facade design correspond with LEED v4.1 and Daylight Availability. It relies on Origami’s technique of papers foldability where the facade morphs through rotation motion to enhance daylight performance. Rhino platform and its plugins Grasshopper and Diva through Daysim and Radiance engines were used for a parametric daylight simulation through two phases for an office facade oriented to east in Cyberjaya, Malaysia. Base cases simulations and simulations for a specific classification of rotation angles and size variable were conducted in first phase through parametric optimization process. 50 cm of radius façade size and 20° of rotation’s angle reached outcome that achieve LEED v4.1 demands. a comparative simulation was conducted in second phase between the previous optimized result which exemplify the static base case with proposed dynamic system where second phase is a current development of phase one. The simulations were conducted on two days of solstice and two days of equinox for each working hours from 8AM–6PM. Lastly, a comparative analysis for the same days of parametric simulation results. Results proved that daylight achieved a better performance in comparison with optimized static case in all seasons approximately.